Characterization of the Wind Resource in the city of Juliaca - Quiñonez Choquecota, José (2019)
In the present paper, a quantitative and qualitative evaluation of the wind resource was carried out in order to characterize the exploitable potential of the wind resource in the area around the city of Juliaca in the Puno region. The data provided for the years 2013-2014 by the National Service of Meteorology and Hydrology of Peru - SENAMHI, of the station located in this city, were analyzed to compare with the database of NASA (Surface Meteorology and Solar Energy. SSE, 2012). The quantitative analysis consisting of the characterization of the average hourly and monthly wind speed for a height of 25 m above the ground, comparing the average monthly speeds of NASA and SENAMHI, shows an average difference of 8.93% during the months of spring and summer, where the wind also exceeds 3 m/s, and the predominant directions of the wind is the west and the east. The qualitative analysis corresponds to the estimation of the wind potential which was carried out with the Weibull distribution, obtaining an average annual power density at 25 m from the ground of 15.91 W/m2, for 50 m this potential is doubled. In short, in the city of Juliaca small wind power generators can be implemented, since the wind resource is not abundant and has variable direction. The characterization made with data from NASA and SENAMHI are similar, therefore, NASA data are reliable to characterize the wind resource of the city of Juliaca.